41 Public reporting of outcomes after percutaneous coronary intervention: is mortality the best outcome?. (6th June 2022) - Kelham, Matthew; Wang, Roy; Kowalczyk, Artur; Rathod, Krishnaraj; OMahony, Constantinos; Wragg, Andrew; Baumbach, Andreas; Mathur, Anthony; Jones, Dan
Abstract : Introduction: Public reporting of 30-day mortality after percutaneous coronary intervention (PCI) imply that death after PCI is a complication for the interventional cardiologist and the hospital. However, in many cases mortality can occur despite receiving optimal care and achieving a successful PCI result. This is especially true in the context of cardiac arrest and cardiogenic shock. This study sought to ascertain the causes of death and the incidence of PCI related mortality within 30 days. Methods: All patients who died within 30 days of PCI between Jan 2019-March 2020 in a tertiary cardiac centre were included. Baseline demographic and procedure related characteristics were recorded. Causes of death were identified through detailed chart review using Academic Research Consortium consensus guidelines. Causes of death were divided into cardiac and noncardiac, with further classification of cardiac deaths into PCI and non–PCI-related groups. PCI-related death was defined as death from complication of procedure such as definite or probable stent thrombosis, coronary dissection or perforation, aneurysm, bleeding and renal failure. All patient deaths were reviewed by a local morbidity and mortality meeting, including at least 3 independent consultant cardiologists not involved in the patients care, and NCEPOD classification of care recorded. Results: Of the 3554 PCI procedures performed during the study period, 96 (2.7%) deaths occurred within 30 days. The majority of these deaths occurred in patients presenting with ST-elevation myocardial infarction (75%). Of the deaths, 67 (69.8%) were cardiac and 29 (30.2%) non-cardiac. Only 8 (8.3%) deaths were attributed to PCI-related complications, representing 0.2% of the total population treated with PCI. Patients with non-PCI related death, compared with PCI-related, presented with a higher incidence of STEMI (78.4% vs 42.9%, p=0.02) and cardiac arrest (51.1% vs 0%, p=0.006). Contemporaneous review of the deaths by a panel of consultant cardiologists characterised clinical care as 'A) Good Practice' in 92.7% of cases. This was lower in the group with PCI-related mortality, although not significantly so. Conclusion: Less than 10% of 30-day mortality following PCI appear attributed to the procedure itself, with more than 90% of patients receiving optimal care. As a result, 30-day mortality following PCI may not represent the best marker of PCI quality and other metrics such as patient reported outcome measures (PROMS) should be explored. Conflict of Interest: None